Tax Avoidance: The Role of Managerial Ability and CEO Overconfidence - Tuljannah, Aulia; Helmy, Herlina (Wahana Riset Akuntansi, 2023)
AbstractPurpose – The purpose of this study is to examine the effect of CEO managerial ability and overconfidence on tax avoidance.Design/methodology/approach – The study was conducted on 120 annual reports of mining sector companies listed on the Indonesian Stock Exchange (IDX) from 2017-2021. Multiple regression was used to test the hypotheses. Tax avoidance was measured by CETR. Managerial ability was measured by firm efficiency and CEO overconfidence is measured by five proxies related to company-specific scores.Findings – This study shows that managerial ability has negative significant effect on tax avoidance. The results reveal that CEO overconfidence has no significant effect on tax avoidance. Managers with high managerial ability will not only increase profits in the short term, but also consider the company's survival in the long term, so; they will reduce tax avoidance activities. Meanwhile, CEO's overconfidence cannot influence the tax management that has been determined by the company.Originality/value– This study attempts to fill the gap in the literature about the influence of management attributes on company decision making in tax avoidance activities. This study indicates that the tax avoidance decision in the company cannot be explained by the executive's psychological characteristics only.Research limitations/Implications – This research is limited to how tax avoidance is influenced by managerial ability and overconfidence in decision making with characteristics related to psychological and internal factors. Future research can add other factors such that can influence decision making in conducting tax avoidance, such as rewards, experience, performance measures and other factors. This study has implications in decision making for policymakers in relation to designing future tax systems to reduce the possibility of companies engaging in tax avoidance practices. Companies are also required to be more transparent in disclosing their performance in generating income to avoid tax avoidance activities.Keywords: Managerial ability, overconfidence, tax avoidance.Article Type: Research Paper.